Town planning regulation in underground urbanistics. Article 2 - Druzhinina, Inna; Kholyavko, Anastasia (project baikal, 2022)
The article presents the main problems of underground construction in the aspect of legal regulation and a possible scenario of their solution by amending the urban planning documentation. It also considers the concept of 3D cadastre and its application in different countries.